2020
DOI: 10.1101/2020.03.28.013797
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterial envelope damage inflicted by bioinspired nanospikes grown in a hydrogel

Abstract: Device-associated infections are one of the deadliest complications accompanying the use of biomaterials, and despite recent advances in the development of anti-biofouling strategies, biomaterials that exhibit both functional tissue restoration and antimicrobial activity have been challenging to achieve. Here, we report the fabrication of bio-inspired bactericidal nanospikes in bacterial cellulose and investigate the mechanism underlying this phenomenon. We demonstrate these structures affects preferentially s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…and in Saccharomyces cerevisiae . It has also been shown that the rigidity of the microbial cells affect their susceptibility to mechanical rupture, ,, for example, Gram-negative bacteria were more sensitive than Gram-positive bacteria, probably due to the cell wall architecture. , Finally, it has been shown that the increased spike density and greater spike height promote the efficacy of the antimicrobial activity of the “nano-spiked” material. However, the precise mechanism leading to microbial cell death is not fully understood.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…and in Saccharomyces cerevisiae . It has also been shown that the rigidity of the microbial cells affect their susceptibility to mechanical rupture, ,, for example, Gram-negative bacteria were more sensitive than Gram-positive bacteria, probably due to the cell wall architecture. , Finally, it has been shown that the increased spike density and greater spike height promote the efficacy of the antimicrobial activity of the “nano-spiked” material. However, the precise mechanism leading to microbial cell death is not fully understood.…”
Section: Resultsmentioning
confidence: 99%
“…Although the EDS-SEM studies indicated the existence of Cu on the surface of the complex, probably responsible for a cationic charge localized on the complex surface, the main antimicrobial effect may be attributed to the modified surface topography of the Cu 2 O–polysaccharide complex, that is, to the spikes 1000 nm in height and 10–20 nm in width, at a density of about 5000 spikes/μm 2 . It seems likely that the high density of the spikes coupled with their height can cause mechanical penetration of the microbial membrane, leading to disruption of membrane permeability and consequently to cell death, as has been shown previously. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, high aspect ratio nanostructures in a hydrogel increase the surface area active for molecular detection, which leads to higher sensitivity and improved signal-to-background ratio in microfluidic and sensing devices. , Similarly, higher surface areas can deliver greater drug doses in a controlled manner compared to conventional flat surfaces . Recently, we have demonstrated that HAR nanostructures can be used for the design of biofouling resistant surfaces inspired by naturally occurring bactericidal nanostructures. , …”
Section: Introductionmentioning
confidence: 99%
“…10 Recently, we have demonstrated that HAR nanostructures can be used for the design of biofouling resistant surfaces inspired by naturally occurring bactericidal nanostructures. 11,12 Photolithography and replica molding techniques have been traditionally used to fabricate nanostructures in hydrogels; however, none of those approaches achieve nanostructures with dimensions below a few microns while maintaining precise control of the size and shape distribution. 13 Indeed, creating homogeneous and reproducible nanosized features with high aspect ratios in soft materials at scale remains challenging.…”
Section: ■ Introductionmentioning
confidence: 99%